The Story of Prophet Yunus (PBUH) in the Qur’an: A Narrative Analysis Using Greimas’s Actantial and Functional Models - Nurahman Majid; Rohanda Rohanda; Muhammad Nurhasan (Gunung Djati Conference Series, 2025)
This study aims to examine the narrative structure of the story of Prophet Yunus (AS) in the Qur’an using A.J. Greimas’s structural semiotic approach, particularly the actantial and functional models. Employing a qualitative-descriptive method, this research analyzes selected verses from Surah As-Saffat (139–148), Al-Anbiya (87–88), and Al-Qalam (48–50) as primary data sources. Data were collected through close reading and literature study, and interpreted through the identification of actantial elements such as subject, object, helper, and opponent, as well as narrative phases including initial situation, transformation, and final situation. The findings reveal that the story of Prophet Yunus is not only rich in theological meaning but also conveys symbolic depth and emotional dynamics, arranged in a systematic narrative structure. Greimas’s actantial schema highlights the functional relationships between narrative roles, while the functional schema traces the transformation of the protagonist from spiritual crisis to redemption and renewed mission. This study affirms that the Qur’anic narrative of Prophet Yunus is intentionally structured and spiritually meaningful, offering insights into the interplay between narrative form and religious content. The results contribute to Qur’anic literary studies by demonstrating how semiotic analysis can uncover layers of meaning that connect linguistic structure with moral and spiritual messages.